THE USE OF IMPORTANCE PERFORMANCE ANALYSIS TO EVALUATE THE SATISFACTION LEVEL OF THE USER OF TRANS JOGJA BUS - Transistari, Ralina (Jurnal Ekonomi, 2017)
The purpose of this research is to evaluate the satisfaction level of the users towards the service quality of Trans Jogja that has been operating for 8 years since the launching. This research used the Importance-Performance Analysis (IPA) method to measure the attributes that are perceived as important by the users compared to the performance all this time. The analysis was illustrated in a scatter diagram with 4 quadrants which showed the position of each attribute of the observed service quality. The attributes of service quality used referred to 5 dimensions of Service Quality, they are reliability, responsiveness, assurance, emphaty, dan tangibles with some compliances to transportation service. The data were collected by using convenience sampling method through the questionnaire contained 23 question items. From 130 questionnaires filled by the users of Trans Jogja bus route 2A and 2B, there were only 97 respondents who are feasible for the analysis. The results showed that in Quadrant I there are 4 attributes of service quality considered important by the users, however, the reality is still out of expectations. Meanwhile, in Quadrant II and III, the attributes and performance considered important by the users have met the expectations, so that the management should maintenance the performance of the attributes. In Quadrant III, there are 6 attributes considered less-important by the users and the performance are not special, so that those are considered as less-prioritized to improve. Meanwhile, in Quadrant IV, there are only 2 attributes considered less-important by the users and perceived excessive for the performance, so that the management can allocate its resources on the other attributes. By these results, it is expected to the management of Trans Jogja bus to be able to concern on the important attributes as concerned by the users to satisfy them, so that the improvement on service quality can be more effective, both from the cost and other resources